The Importance of Gestational Sac Size of Ectopic Pregnancy in Response to Single-Dose Methotrexate. (14th May 2013) - Kimiaei, Parichehr; Khani, Zahra; Marefian, Azadeh; Gholampour Ghavamabadi, Maryam; Salimnejad, Maryam
Abstract : This retrospective cohort study was designed in a selective group of 185 patients diagnosed with and treated for ectopic pregnancy. Intramuscular administration of a single dose of methotrexate (50 mg/m 2 ) was performed to measure predictors of failure or resistance to treatment necessitating surgical intervention. During the time of treatment with a single dose of MTX, 20 patients (10.8%) failed to response, in which 6 of 20 (30%) indicated side effects to MTX and rupture of the ectopic pregnancy. Remaining cases (n = 14 ) showed resistance to the drug; the level of β -hCG did not fall at least 15% during 7 days after treatment and necessitated laparotomy. In backward-step analysis by multiple logistic regressions of various types of predictor factors, size of gestational sac (coefficient = 1.91, OR = 6.78, 95% confidence interval = 3.18–8.22) and baseline level β -hCG (coefficient = 1.60, OR = 5.0, 95% confidence interval = 4.26–6.72) had significant correlation with leading EP patients failing to response to MTX. This study suggests that further investigation for finding relative contraindications of MTX treatment in EP women should be considered on the gestational sac size because other variables are in the causal pathway of this variable.